Xenon/remifentanil anesthesia protects against adverse effects of losartan on hemodynamic challenges induced by anesthesia and acute blood loss - Francis, Roland C. E.; Philippi-Hoehne, Claudia; Klein, Adrian; Pickerodt, Philipp A.; Reyle-Hahn, Matthias S.; Boemke, Willehad (Shock, 2010)
The authors aimed to test the hypothesis that xenon anesthesia limits adverse hypotensive effects of losartan during acute hemorrhage. In six conscious unsedated Beagle dogs, the systemic and pulmonary circulation were monitored invasively, and two subsequent 60-min hypotensive challenges were performed by (a) induction (propofol) and maintenance of anesthesia with isoflurane/remifentanil or xenon/remifentanil and by (b) subsequent hemorrhage (20 mL kg-1 within 5 min) from a central vein. The same amount of blood was retransfused 1 h after hemorrhage. Experiments were performed with or without acute angiotensin II receptor subtype 1 blockade by i.v. losartan (100 μg·kg-1·min-1) starting 45 min before induction of anesthesia. Four experiments were performed in each individual dog. Xenon/remifentanil anesthesia provided higher baseline mean arterial blood pressure (85 ± 6 mmHg) than isoflurane/remifentanil anesthesia (67 ± 3 mmHg). In losartan-treated animals, isoflurane/remifentanil caused significant hypotension (42 ± 4 mmHg for isoflurane/remifentanil vs. 71 ± 6 mmHg for xenon/remifentanil). Independent of losartan, hemorrhage did not induce any further reduction of mean arterial blood pressure or cardiac output in either group. Spontaneous hemodynamic recovery was observed in all groups before retransfusion was started. Losartan did not alter the adrenaline, noradrenaline, and vasopressin response to acute hemorrhage. Losartan potentiates hypotension induced by isoflurane/remifentanil anesthesia but does not affect the hemodynamic stability during xenon/remifentanil anesthesia. Losartan does not deteriorate the hemodynamic adaptation to hemorrhage of 20 mL kg-1 during xenon/remifentanil and isoflurane/remifentanil anesthesia. Therefore, xenon/remifentanil anesthesia protects against circulatory side effects of losartan pretreatment and thus may afford safer therapeutic use of losartan during acute hemorrhage. Copyright © 2010 by the Shock Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: angiotensin II receptor antagonist; Hemorrhage; hypotension; isoflurane